WORD FORMATION PROCESSES IN ENTERTAINMENT ARTICLES IN THE JAKARTA POST - ASTRIDYA, FARA WAHYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Morphology, Word Formation Process, Entertainment, Jakarta Post.Language is related to word formation processes because it is the process of creating new words and new uses of the old words and also how new words are being formed. This research was about word formation processes in entertainment articles. There are two problems to be solved in this study, namely: (1) what word-formation processes of the words found in Entertainment Article in Jakarta Post; (2) what types of word-formation processes frequently appear in entertainment article in Jakarta Post.The researcher used the theory of Yule (2010) to analyze this research. The researcher took 11 articles of entertainment in Jakarta Post as the data. This research used qualitative research to describe the terms in entertainment articles based on word formation processes. Qualitative research is used to find out the words of word formation processes in the entertainment articles in Jakarta Post. This study reveals that there were derivation is the most frequently types that appears in entertainment articles. The writer found 25 words of derivation, 21 of compounding, 7 words of borrowing, 3 words of acronyms and 1 blending. The research in field of morphology especially word formation process is a beneficial research because it takes an important part of the word formulation in language. The next researcher can try to find out theory based on the different expert. The writer also suggests for the next researchers who are interested in doing further research in this area to conduct the research with more variation in data collection.